KEMISKINAN: KONSEP, PENGUKURAN DAN KEBIJAKAN* - Marcelinus Molo (Populasi, 1995)
The incidence of poverty within a society is, in fact, social problem both for those who are living under a defined poverty line, and for those who are better off. As a consequence, poverty becomes a central issue in economic and social policies.Poverty has stimulated researchers to update the measures. The article concentrates on the conceptual and operational definition, measurements, factors underlying the existance of poverty, and relevant policies towards the alleviation of poverty.